Identity and well‐being in the skilled crafts and trades. (13th March 2022) - Binder, Martin; Blankenberg, Ann‐Kathrin
Abstract: We analyze the extent to which occupational identity is conducive to worker well‐being. Using a unique survey data set of individuals working in the German skilled crafts and trades (2017–2018, n = 757), we use a novel occupational identity measure that captures identity more broadly than just referring to organizational identification and social group membership, but rather comprises personal and relational elements inherent in one's work. The latter are linked to significant social interactions a worker has in their job and the former to specific work characteristics of the work conducted itself. We find that higher job satisfaction is related to a stronger sense of occupational identity in our sample. This relationship is quite sizable and robust across model specifications, whereas income is not associated with job satisfaction in most models. Occupational identity is positively associated with a number of work characteristics, viz. task significance, task and skill variety, as well as social support, and our analysis shows that identity mediates the influence of these characteristics with regard to job satisfaction.